Penerapan Model Pembelajaran Children Learning In Science (CLIS) untuk Meningkatkan Motivasi Belajar IPA Siswa Kelas IV SDN Gentan 03 Tahun Ajaran 2015/2016 - Kartika, Marissa Yudha (2016)
The Faculty of Education, University Muhammadiyah Surakarta, February, 2016. The purpose of this research is to increase student's motivation. This type of research is a classroom action research. The subjects research are teachers and fourth grade students. Technique collecting data using interviews, observation, test and documentation. Data analysis technique used is descriptive analysis techniques. While the validity data using triangulation. The results showed an increase of student motivation, which include: Their willingness and desire to learn or a sense of excitement in the pre cycle 37,00% , the first cycle 59,24% and the second cycle of 82,61%, Interest in learning activities in the pre cycle 39,13%, the first cycle 60,87% and the second cycle of 83,15%, Persevering in doing on pre cycle 44,57%, the first cycle 61,41% and the second cycle of 80,43%, Have confidence in the pre cycle 37,00%, the first cycle 59,97% and the second cycle of 75,54%, Not easily discouraged when facing difficulties in learning in the pre cycle 47,83%, the first cycle 61,95% and the second cycle of 79,89%. Models Children Learning In Science show improve student learning outcomes, pre cycle 43,48% and increased in the second cycle 91,30%. The conclusion of this study is through the application of learning models Children Learning In Science) can increase the motivation and learning outcomes to learn science.